The Anticipation of Converging Industries A Concept Applied to Nutraceuticals and Functional Foods - Curran, Clive-Steven.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The blurring of boundaries between hitherto distinct scientific disciplines, technologies or markets is a common and powerful phenomenon. Subjects of this convergence often change consumer behaviours, favouring products and platforms with multiple functions. The Anticipation of Converging Industries provides a detailed focus on the triggers, drivers and consequences of convergence to create a more concise definition of convergence.   This detailed analysis includes a specifically developed toolbox for ‘convergence foresight’, creating a forecasting method for convergence trends. With the focus on the chemical, biotechnological and pharmaceutical industries, several indicators of convergence in the areas of Nutraceuticals/Functional Foods, Cosmeceuticals and ICT are derived from samples including over 1million patents and scientific publications.   By supporting this methodical approach with real world data, The Anticipation of Converging Industries is perfect for industry practitioners looking for a competitive edge in the present and for the future. Similarly, academics will find a comprehensive theoretical concept for better understanding the underlying rationale of convergence at their disposal.
1.Introduction -- 2.Convergence -- 3.Anticipating Convergence -- 4.Conceptual Framework and Research Design -- 5.Analysis and Results -- 6.Discussion of Findings and Implications for Theory and Practice -- 7.Summary and Conclusion -- App. 1. Hierarchical construction of IPCs.
Keywords: Engineering economics; Engineering economy; Economic policy; Management; Industrial management; Pharmaceutical technology; Life sciences; Behavioral sciences; Engineering Economics, Organization, Logistics, Marketing; R & D/Technology Policy; Innovation/Technology Management; Pharmaceutical Sciences/Technology.; Life Sciences, general; Behavioral Sciences